The role of the mTOR pathway in breast cancer stem cells (BCSCs): mechanisms and therapeutic potentials - Chen Zhang; Shu Xu; Chuanzheng Yin; Shaobo Hu; Pian Liu (Stem Cell Research & Therapy)
Abstract Breast cancer remains the most frequently diagnosed cancer globally, exerting a profound impact on women’s health and healthcare systems. Central to its pathogenesis and therapeutic resistance are breast cancer stem cells (BCSCs), which possess unique properties such as self-renewal, differentiation, and resistance to conventional therapies, contributing to tumor initiation, metastasis, and recurrence. This comprehensive review elucidates the pivotal role of the mechanistic target of rapamycin (mTOR) pathway in regulating BCSCs and its implications for breast cancer progression and treatment resistance. We explore the cellular mechanisms by which mTOR influences metastasis, metabolism, autophagy, and ferroptosis in BCSCs, highlighting its contribution to epithelial-to-mesenchymal transition (EMT), metabolic reprogramming, and survival under therapeutic stress. On a molecular level, mTOR interacts with key signaling pathways including PI3K/Akt, Notch, IGF-1R, AMPK, and TGF-β, as well as regulatory proteins and non-coding RNAs, orchestrating a complex network that sustains BCSC properties and mediates chemoresistance and radioresistance. The review further examines various therapeutic strategies targeting the mTOR pathway in BCSCs, encompassing selective PI3K/Akt/mTOR inhibitors, monoclonal antibodies, natural products, and innovative approaches such as nanoparticle-mediated drug delivery. Clinical trials investigating mTOR inhibitors like sirolimus and combination therapies with agents such as everolimus and trastuzumab are discussed, underscoring their potential in eradicating BCSCs and improving patient outcomes. Additionally, natural compounds and repurposed drugs offer promising adjunctive therapies by modulating mTOR activity and targeting BCSC-specific vulnerabilities. In conclusion, targeting the mTOR pathway presents a viable and promising avenue for enhancing breast cancer treatment efficacy by effectively eliminating BCSCs, reducing tumor recurrence, and improving overall patient survival. Continued research and clinical validation of mTOR-targeted therapies are essential to translate these insights into effective clinical interventions, ultimately advancing personalized cancer management and therapeutic outcomes for breast cancer patients.